Internet connectivity disruption in Turkey (Turkey) - Voidly (Voidly Global Censorship Index, 2026)
CRITICAL severity disruption detected in Turkey. Data sourced from IODA.
Network Disruption Incident ID: TR-2026-0053. Severity: critical. Confidence: 65%